Escala de Auto-Estima Rosenberg-UNIFESP/EPM, Oral Health Impact Profile em idosos com overdentures mandibulares - Parenti Filho, Antonio [UNIFESP] (2010)
INTRODUCTION: The advent of endosseous dental implants has allowed the success of oral rehabilitation in order to obtain a better stability, retention, comfort, aesthetic, phonetic, functional capacity and well-being, with consequent longevity of oral health. The validated questionnaires about quality of life are proving to be increasingly indispensable and able to measure quantitatively the quality of life, as scientific content, through statistical data. OBJECTIVES: To evaluate the quality of life and self-esteem in elderly patients who have replaced conventional dentures for mandibular overdentures. METHODS: Twenty-seven patients (15 in study group and 12 in control group) were submitted to mandibular overdentures and were evaluated through questionnaires of quality of life in a self-administered attended: SF- 36, OHIP-49 and Rosenberg-UNIFESP/EPM Self-Esteem Scale. RESULTS: In the Wilcoxon test, a non-parametric test, statistical differences were observed, to the OHIP-49, in the study group to the following domains: functional limitation (p=0, 010), physical pain (p=0,020), physical disability (p=0,021), and psychological disability (p=0,040). In the Mann Whitney test, also a nonparametric test, statistical differences were observed, to the OHIP 49, second phase, to the following domains: functional limitation (p<0.001), physical pain (p=0,014), psychological discomfort (p=0,005), disability (p=0,022), psychological disability (p=0,007), social disability (p-0,031), disability (p=0,018), and total p (p=0,001). There were no statistical differences in the Rosenberg-UNIFESP/EPM Self-esteem Scale and SF-36. CONCLUSION: There was a positive impact on quality of life, except in relation to self-esteem, in elderly who have replaced conventional dentures for mandibular overdentures.